The choice of new treatments in autoimmune hemolytic anemia: how to pick from the basket? - Berentsen, Sigbjørn; Fattizzo, Bruno; Barcellini, Wilma (Frontiers in Immunology, 2023)
Autoimmune hemolytic anemia (AIHA) is defined by increased erythrocyte turnover mediated by autoimmune mechanisms. While corticosteroids remain first-line therapy in most cases of warm-antibody AIHA, cold agglutinin disease is treated by targeting the underlying clonal B-cell proliferation or the classical complement activation pathway. Several new established or investigational drugs and treatment regimens have appeared during the last 1-2 decades, resulting in an improvement of therapy options but also raising challenges on how to select the best treatment in individual patients. In severe warm-antibody AIHA, there is evidence for the upfront addition of rituximab to prednisolone in the first line. Novel agents targeting B-cells, extravascular hemolysis, or removing IgG will offer further options in the acute and relapsed/refractory settings. In cold agglutinin disease, the development of complement inhibitors and B-cell targeting agents makes it possible to individualize therapy, based on the disease profile and patient characteristics. For most AIHAs, the optimal treatment remains to be found, and there is still a need for more evidence-based therapies. Therefore, prospective clinical trials should be encouraged.